Basic Training Group III Patterns in the Network (Online): Perceptions of Participant Satisfaction and Learning Outcomes - Bailah Bailah; Bambang Niko Pasla (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2020)
This study aims to determine how the success rate of implementing the online pattern latsar compared to the facial pattern latsar that has been done so far. Measurement of the effectiveness/success rate of latsar is done by evaluating using the Kirkpatrick reaction level and learning level approach. This study uses a mixed mix approach of quantitative and qualitative. Data were collected by filling out questionnaires and secondary data studies. Subjects for this study were participants of CPNS Class III Batch I Tanjung Jabung Barat Regency 2020. The informants in this study were 40 (forty) participants and the organizing committee at BKPSDM, Tanjung Jabung Barat Regency. The data analysis technique was carried out by using qualitative data that was converted into quantitative data, data classification, formulating research results, and analyzing research results. The results of the research on the reaction level showed that 71.95% of Latsar participants showed a